(untitled) (Journal of Economic Research & Business Administration, 2022)
The number and accessibility of sports facilities impacts the development of mass sports and a healthy lifestyle in Kazakhstan. In this regard, the purpose of this study is to analyze the current state of the sports infrastructure in Kazakhstan. Based on statistical data, an inter-regional analysis of the equipment with sports facilities and facilities was carried out, recommendations were made on the development of sports infrastructure in Kazakhstan. The value of this study lies in the fact that its results can be used in future studies that assess the dynamics of the development of mass sports and sports infrastructure in Kazakhstan. The paper considers the features of the development of sports infrastructure in Kazakhstan and justifies expanding the network of sports facilities in regions of Kazakhstan. The analysis based on the number of sports facilities, the number of people systematically involved in sports, and the budgetary expenses of local executive bodies for improving sports facilities. The article is of interest researchers involved in the development of mass sports and the sports industry in the Republic of Kazakhstan. Keywords: sports infrastructure, classification of sports facilities, the one-time capacity of a sports facility, systematic sports, expenses for the development of sports facilities.